PELAKSANAAN DISCHARGE PLANNING DENGAN KEPUASAN PASIEN HIPERTENSI DI RUMAH SAKIT PINGGIRAN SUNGAI BARITO - Setiawan, Herry (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Patient satisfaction is influenced by how patients perceive the services they receive during the treatment period. Discharge planning is carried out during the patient's treatment period. Failure to provide discharge planning will put the patient at risk of serious illness, life threatening and physical dysfunction.The purpose of the study was to determine the relationship between the implementation of discharge planning and the satisfaction of hypertensive patients at a hospital on the outskirts of the Barito River. This quantitative study used a correlational design with a cross sectional approach with purposive sampling, involving 71 respondents in RSUDUlin Banjarmasin, RSUD dr. Moch Ansari Saleh Banjarmasin, and RSUD Sultan Suriansyah Banjarmasin from July to November 2020. The results showed that patients who were hospitalized in hospitals who received good discharge planning were mostly in the satisfied category, 28 respondents (39.44%), Getting good discharge planning is mostly in the dissatisfied category, 18 respondents (25.35%), less getting good discharge planning is in the dissatisfied category, 17 respondents (23.94%), and less getting discharge planning which were both included in the satisfied category, a number of 8 respondents (11.27%). There is a significant relationship between the implementation of discarge planning and patient satisfaction (p = 0.020).